2016
DOI: 10.7566/jpsj.85.034710
|View full text |Cite
|
Sign up to set email alerts
|

Properties and Collapse of the Ferromagnetism in UCo1−xRuxAl Studied in Single Crystals

Abstract: We have investigated the ferromagnetic (FM) phase which suddenly develops in UCo1-xRuxAl and is isolated by paramagnetic regions on both sides from the parent UCoAl and URuAl. For that purpose we have grown high quality single crystals with x = 0.62, 0.70, 0.74, 0.75 and 0.78. The properties of the FM phase have been investigated by microscopic and macroscopic methods. Polarized neutron diffraction on a single crystal with x = 0.62 revealed the gradual growth of the hybridization between U and T-site in the U … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…Magnetic x-ray and photoemission measurements also certify the presence of electronic correlations (25,26). Furthermore, previous work has shown substantial anomalous Hall conductivity (AHC) for dopings close to the quantum-phase transition (21). Here, we examine x = 0.2 with a critical temperature (T c) of 56 K, close to the optimal value in the series.…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations
“…Magnetic x-ray and photoemission measurements also certify the presence of electronic correlations (25,26). Furthermore, previous work has shown substantial anomalous Hall conductivity (AHC) for dopings close to the quantum-phase transition (21). Here, we examine x = 0.2 with a critical temperature (T c) of 56 K, close to the optimal value in the series.…”
Section: Introductionmentioning
confidence: 76%
“…In our exploration of materials we found that the layered distorted kagome lattice system UCo 1−x Ru x Al in the ZrNiAl structure type (shown in Fig. 1A) satisfies all the above crite- (20,21). Members of the entire alloy series show relatively large Sommerfeld coefficients γ of ∼50 mJ/mol K 2 (21-24), indicating that charge carriers are moderately heavy.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…It is considered here that the spin-fluctuation behavior should be derived dominantly from the U 5f electrons as a plausible interpretation. However, the magnetic stability of UCoAl is very sensitive to the elemental substitution for Co and Al atoms [17][18][19][20][21]. For example, in the case of the UCo 1−x Ru x Al system [19,21], the ferromagnetism already appears for very low Ru content with x = 0.01 and persists up to x ∼ 0.75, although both of the parent compounds, UCoAl and URuAl, are in a PM ground state.…”
Section: Introductionmentioning
confidence: 99%